Liver abscesses in feedlot cattle: further delineation of etiology and pathogenesis, and evaluations of potential antimicrobial alternatives for prevention - Salih, Harith Mohammed Saleem (My University, 2025)
Liver abscesses are a significant economic concern in feedlot cattle fed high-grain, low-roughage diets, with an estimated annual loss of over $60 million in the beef industry due to reduced feed efficiency, lower carcass value, and increased management costs. The primary causative agents of liver abscesses include Fusobacterium necrophorum subspecies (necrophorum and funduliforme), Trueperella pyogenes, and Salmonella enterica serotype Lubbock. These bacteria translocate from the rumen and hindgut to the liver via the portal vein, where they establish infections under anaerobic conditions. Although tylosin, a macrolide antibiotic, is commonly used in feed to reduce liver abscess prevalence, growing concerns over the emergence of antimicrobial resistance highlight the urgent need for alternative control strategies. This study aimed to investigate liver abscess pathogenesis and evaluate the antimicrobial potential of sorghum phenolics, other phytophenols, and probiotics as natural alternatives to antibiotics in feedlot cattle. To enhance understanding of liver abscess pathogenesis, the prevalence and tissue distribution of key pathogens were assessed. Results revealed that F. necrophorum subsp. necrophorum exhibited a high prevalence in liver abscesses (86.4%) compared to ruminal (6.25%) and colonic tissues (19.79%), whereas subsp. funduliforme was more prevalent in ruminal (41.66%) and colonic tissues (33.3%) than in liver abscesses (21.8%). T. pyogenes was predominantly isolated from liver abscesses (35.4%) and ruminal tissues (11.4%) but was absent in colonic tissues. Enrichment methods significantly improved the detection of these bacterial species. Probiotic culture supernatants, particularly from Lactobacillus helveticus, demonstrated strong antimicrobial activity, inhibiting the growth of F. necrophorum, T. pyogenes, and S. enterica. Similarly, phenolic extracts from grape seed, green tea, and rosemary exhibited dose-dependent inhibitory effects on these pathogens, with green tea phenolics showing the highest antimicrobial activity. Notably, green tea achieved minimum inhibitory concentrations of 6.25–12.5 µg/ml for T. pyogenes and demonstrated robust inhibition of both Fusobacterium subspecies and S. enterica. In addition, phenolic extracts from black and brown sumac sorghum (Sorghum bicolor) showed promising inhibitory effects on F. necrophorum and T. pyogenes, though they were less effective against S. enterica. These findings underscore the potential of probiotics such as L. helveticus and plant-derived phenolic compounds, particularly green tea and sorghum, as natural feed supplements for controlling liver abscesses in cattle. Future research should investigate the mechanisms of bacterial translocation from the rumen and hindgut to the liver, explore metagenomic approaches to elucidate the role of minor pathogens, and conduct in vivo studies to validate the efficacy of these alternatives. Such efforts will contribute to improving cattle health and mitigating economic losses in the beef production system.
Keywords: Liver abscesses; Pathogenesis; Feedlot cattle; Antibiotic alternatives; Phytophenols; Probiotics